2009
DOI: 10.2320/matertrans.mbw200829
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatment of TiH<SUB>2</SUB> Powder to Control Decomposition Phenomenon for Aluminum Foam Fabrication by Melt Route

Abstract: TiH 2 powder has been used to fabricate aluminum foams as a blowing agent for more than two decades. The aim of this paper is to understand the detailed decomposition behavior of TiH 2 powder and to control the phenomenon by a heat treatment for the fabrication of fine aluminum foams by the melt route. TiH 2 powders whose qualities were different, were characterized using TG-DTA and XRD. As heat treatment factors, temperature and time were applied. We have found differences in the decomposition behavior betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Silicon dioxide powder with particles size from 40 to 80 nm was selected as reinforcement material because of its good wettability with aluminum alloys. TiH 2 powder was used as foaming agent with purity more than 98% and was heat treated at 450°C for 3 h to improve gas releasing behavior [6,19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon dioxide powder with particles size from 40 to 80 nm was selected as reinforcement material because of its good wettability with aluminum alloys. TiH 2 powder was used as foaming agent with purity more than 98% and was heat treated at 450°C for 3 h to improve gas releasing behavior [6,19].…”
Section: Methodsmentioning
confidence: 99%
“…Kadoi [6] showed that the decomposition of TiH 2 starts at around 420°C, but in aluminum foam fabrication by the melt route technique, the samples are heated between 600°C and 700°C. Thus, the temperature difference between the TiH 2 decomposition and foam fabrication strongly influences the yield and the foaming phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…36) However, it is difficult to evaluate how each pore structure affects the mechanical properties of Al foam. In particular, the Al foam produced by the casting 7,8) or precursor 9,10) method undergo a foaming process in which it is slightly difficult to control the pore structures. Thus, there are some variations in the mechanical properties of the obtained Al foam.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, there were virtually no oxide phases detectable in the TiH 2 -6Al-4V powder mixture below 898 K (625°C). After that, due to less release of H 2 from the initial TiH 2 powder and increased temperature, oxide phases [Ti 3 O, Ti 6 O, and TiO 2 (H: hexagonal with a = 2.96 Å , c = 4.85 Å )] [18][19][20][21][22][23] started to build up on the freshly exposed Ti powder surfaces but the process still occurred to a less extent than the case with the HDH Ti-6Al-4V alloy. The dehydrogenation of TiH 2 has clearly affected the formation and/or growth of oxide films on the particle surfaces.…”
mentioning
confidence: 99%
“…The oxides were determined to be TiO 2 (tetragonal with a = 4.59 Å and c = 2.96 Å ), [18][19][20][21] showing a preferential growth along its (200) plane. At about 898 K (625°C), the presence of other titanium oxide phases, Ti 3 O (hexagonal with a = 5.15 Å and c = 9.56 Å ) [18,19,22] and Ti 6 O (hexagonal with a = 5.13 Å and c = 9.48 Å ), [22,23] were detected. Ti 3 O and Ti 6 O have almost identical crystal structure and lattice parameters, making their peaks often overlap.…”
mentioning
confidence: 99%